Plasma succinate is a predictor of mortality in critically injured patients. Issue 3 (September 2017) - D'Alessandro, Angelo; Moore, Hunter B.; Moore, Ernest E.; Reisz, Julie A.; Wither, Matthew J.; Ghasasbyan, Arsen; Chandler, James; Silliman, Christopher C.; Hansen, Kirk C.; Banerjee, Anirban
Abstract : BACKGROUND: Trauma is the leading cause of mortality under the age of 40 years. Recent observations on metabolic reprogramming during hypoxia and ischemia indicate that hypoxic mitochondrial uncoupling promotes the generation of succinate, which in turn mediates reperfusion injury and inflammatory sequelae upon reoxygenation. Plasma levels of succinate significantly increase in response to trauma and hemorrhage in experimental models and clinical samples, suggesting that succinate may represent a candidate marker of systemic perfusion in trauma. METHODS: Quantitative mass spectrometry-based metabolomics was used to quantify succinate and lactate in 595 plasma samples from severely injured patients enrolled at the Denver Health Medical Center, a Level I trauma center in Denver, Colorado. RESULTS: A total of 95 severely injured patients were sampled for up to 10 time points (595 total samples), from field blood to 7 days postinjury. Results indicate that plasma levels of succinate increased up to 25.9-fold in deceased patients versus the median of the surviving patients ( p = 2.75e-100; receiver operating characteristic area under the curve, 0.911). On the other hand, only 2.4-fold changes increases in lactate were observed ( p = 5.8e-21; area under the curve, 0.874). CONCLUSION: Succinate represents a uniquely sensitive biomarker of postshock metabolic derangement and may be an important mediator of sequelae. Level of evidence: Prognostic study, level III. Abstract : Supplemental digital content is available in the text.